TEACHERS’ INSTRUCTIONAL COMPETENCY DEVELOPMENT TO PROMOTE HIGHER ORDER THINKING FOR SECONDARY STUDENTS: การพัฒนาสมรรถนะการจัดการเรียนรู้ของครูเพื่อส่งเสริมการคิดขั้นสูง สำหรับผู้เรียนชั้นมัธยมศึกษา - Onthanee, Angkana (Journal of Education and Innovation, 2021)
This research aims to 1) develop teachers’ instructional competency to promote higher order thinking for secondary students, 2) study the effect of developing teachers’ instructional competency, and 3) study the success factors in implementing the development of teachers’ instructional competency. The participants consisted of 30 secondary school teachers who enroll in the project. The research was divided into 2 steps: Step 1: Development of teachers’ instructional competency to promote higher order thinking for secondary students. Step 2: Study the results of teachers’ instructional competency to promote higher order thinking for secondary students. The research instruments consisted of teacher’s Competency Assessment Form and field note. The data were analyzed by using t-test dependent and content analysis. The research findings were as follow: 1) Teachers’ instructional competency to promote higher order thinking consist of learning process design, the ability to organize learning activities, the ability to provide a learning environment for students and the ability to assess students’ higher-order thinking. Teachers’ instructional competency to promote higher order thinking for secondary students in the post-test were higher than the pre-test with statistical level of .01, 2) The teachers had the instructional competency to promote higher order thinking at high level ( = 4.42), and 3) There are four factors of success in developing teachers’ instructional competency to promote higher-order thinking for secondary school students: 1) academic leadership of school administrators; 2) perceptions of teaching behavior; 3) teacher-student relationship; and 4) performance motivation.